МУЗЫКАЛЬНОЕ ИСКУССТВО – КАК ДЕЙСТВЕННОЕ СРЕДСТВО МУЗЫКАЛЬНО - ЭСТЕТИЧЕСКОГО ВОСПИТАНИЯ УЧАЩИХСЯ НАЧАЛЬНЫХ КЛАССОВ - Сайтбекова, С.; Сапарбаева, Т. (SCIENCE and SOCIETY, 2021)
This article discusses the issues of musical and aesthetic education of primary school students, by teaching choral singing in a music lesson in secondary schools.